An IT System for the Remote Burden Optimization of Foundry Furnaces - Ziółkowski, Eugeniusz (Journal of Casting & Materials Engineering, 2021)
The burden calculations for foundry furnaces are one of the most important steps in preparing the production of liquid casting alloys. These calculations, due to the usually large number of input materials and chemical elements, are realized by numerical methods. These methods are implemented in some spreadsheets, universal mathematical programs or in specialized programs for foundry engineering. The paper describes a computerized system for remote calculations of optimal burden. The technological, economic, and organizational features of implementing IT system have been presented, also taking into account its safety of use.